Epidemiological characterization of COVID-19 in a health area. Jiguaní. January-August, 2021 - Rachel Roxana Domínguez-Rivero; Yanier Espinosa-Goire; José Manuel Padilla-González; Andy Guillermo Paumier-Durán; Elizabeth de la Caridad Milán-Villegas (Gaceta Médica Estudiantil, 2023)
Introduction: COVID-19 has been considered the most complex health crisis in the last hundred years. It marked a different era due to its impact on human behavior and society in general. It evidenced the capacity for progress and resistance of human beings in the face of the great challenges that arose. Objective: to characterize clinically and epidemiologically the patients confirmed with COVID-19 belonging to the health area of the "Edor de los Reyes" polyclinic from January to August 2021. Method: an observational, descriptive, cross-sectional study was carried out, whose universe consisted of the 676 patients who were positive in the real-time polymerase chain reaction test for COVID-19, with or without symptoms. Variables such as: incidence, age, sex and hospital stay were used. It used the descriptive statistic. Results: the Jiguaní Sur popular council classified 43.93% of the total confirmed cases as very high risk. The female sex predominated with 51.6% and the most representative age was between 50 and 59 years with 19.8%. 43.9% of the diagnosed patients became infected within the family environment. The most frequent symptom on admission was cough, for 57.4%. Conclusions: COVID-19 has a high potential for spread. It comprises a symptomatic courtship associated with a high number of sequelae that impair the biopsychosocial development of the individual. The systematic updating of the epidemiological behavior and the analysis of its evolution serve as a guide for the development of health programs.